Training the Trainers of Tomorrow Today - driving excellence in medical education. Issue 1 (27th August 2013) - Fellow-Smith, Elizabeth; Beveridge, Ed; Hogben, Katy; Wilson, Graeme; Lowe, John; Abraham, Rachel; Ingle, Digby; Bennett, Danielle; Hernandez, Carol
Abstract: Training the Trainers of Tomorrow Today (T4) is a new way to deliver "Training for Trainers". Responding to local dissatisfaction with existing arrangements, T4 builds on 3 essential requirements for a future shape of training: 1. Clinical Leadership and a Collaborative Approach 2. Cross-Specialty Design and Participation 3. Local Delivery and Governance Networks Design principles also included: 3 levels of training to reflect differing needs of clinical supervisors, educational supervisors and medical education leader, mapping to GMC requirements and the London Deanery's Professional Development Framework; alignment of service, educational theory and research; recognition of challenges in delivering and ensuring attendance in busy acute and mental health settings, and the development of a faculty network. The delivery plan took into account census of professional development uptake and GMC Trainee Surveys. Strong engagement and uptake from the 11 Trusts in NW London has been achieved, with powerful penetration into all specialties. Attendance has exceeded expectations. Against an initial 12 month target of 350 attendances, 693 were achieved in the first 8 months. Evaluation of content demonstrates modules are pitched appropriately to attendees needs, with positive feedback from trainers new to the role. Delivery style has attracted high ratings of satisfaction: 87% attendees rating delivery as "good\excellent". External evaluation of impact demonstrated improved training experiences through changes in supervision, the learning environment and understanding of learning styles. We have addressed sustainability of the programme by advertising and recruiting Local Faculty Development Trainers. Volunteer consultants and higher trainees are trained to deliver the programme on a cascade model, supported by the Specialty Tutors, individual coaching and educational bursaries. The Trainers are local champions for excellence in training, provide a communication between the programme and local providers, are a repository of expertise in their service, and trouble shoot local barriers to engagement.